The insecticidal activity of recombinant nemertide toxin α-1 from Lineus longissimus towards pests and beneficial species. (15th July 2021) - Bell, Jack; Sukiran, Nur Afiqah; Walsh, Stephen; Fitches, Elaine C.
Abstract: The nemertide toxins from the phylum Nemertea are a little researched family of neurotoxins with potential for development as biopesticides. Here we report the recombinant production of nemertide α-1 (α-1), a 65-residue inhibitor cystine knot (ICK) peptide from Lineus longissimus, known to target insect voltage-gated sodium channels. The insecticidal activity of α-1 was assessed and compared with the well characterised ICK venom peptide, ω-atracotoxin/hexatoxin-Hv1a (Hv1a). α-1 elicited potent spastic paralysis when injected into cabbage moth ( Mamestra brassicae ) larvae; conferring an ED50 3.90 μg/larva (10.30 nmol/g larva), followed by mortality (60% within 48 h after 10 μg injection). By comparison, injection of M. brassicae larvae with recombinant Hv1a produced short-lived flaccid paralysis with an ED50 over 6 times greater than that of α-1 at 26.20 μg/larva (64.70 nmol/g larva). Oral toxicity of α-1 was demonstrated against two aphid species ( Myzus persicae and Acyrthosiphon pisum ), with respective LC50 values of 0.35 and 0.14 mg/mL, some 6-fold lower than those derived for recombinant Hv1a. When delivered orally to M. brassicae larvae, α-1 caused both paralysis (ED50 11.93 μg/larva, 31.5 nmol/g larva) and mortality. This contrasts with the lack of oral activity of Hv1a, which when fed to M. brassicae larvae had no effect on feeding or survival. Hv1a has previously been shown to be non-toxic by injection to the beneficial honeybee ( Apis mellifera ). By contrast, rapid paralysis and 100% mortality was observed following injection of α-1 (31.6 nmol/g insect). These results demonstrate the great potential of naturally occurring non-venomous peptides, such as α-1, for development as novel effective biopesticides, but equally highlights the importance of understanding the phyletic specificity of a given toxin at an early stage in the quest to discover and develop safe and sustainable pesticides. Highlights: Nemertide toxin α-1 from Lineus longssimus was produced as a recombinant peptide using the expression host Pichia pastoris. In artificial diet bioassays recombinant α-1 showed acute oral toxicity to aphids ( Acyrthosiphon pisum and Myzus persicae ). Oral toxicity of α-1 to aphids was 6-fold greater than the spider venom peptide ω-atracotoxin/hexatoxin-Hv1a. Recombinant α-1 was found to be equally toxic to Mamestra brassicae larvae and adult Apis mellifera in injection bioassays.